2009
DOI: 10.2165/00148581-200911040-00002
|View full text |Cite
|
Sign up to set email alerts
|

Non-Infectious Pediatric Uveitis

Abstract: Pediatric non-infectious uveitis remains a rare but potentially sight-threatening group of diseases. However, early screening and treatment can improve outcomes. No single agent has proven to be efficacious in all cases. A wide variety of long-term immunomodulatory treatments are available; these agents differ in both their potency and side effect profiles. Corticosteroids remain an extremely valuable form of treatment in the short-term management of uveitis. Other major groups of immunomodulatory treatments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 112 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Neither ciclosporin nor mycophenolate mofetil is very effective in controlling joint manifestations of JIA in children. 19 More recently, animal models and corroborative human evidence 23 support the role of tumour necrosis factor alpha (TNF-α) in the aetiopathogenesis of uveitis and, moreover, the potential value of its inhibition as a therapeutic intervention. 24 Studies on experimental models of autoimmune uveitis have demonstrated that TNF-α plays a pivotal role in pathogenesis of intraocular inflammation, 23 which has been borne out in treatment of adult uveitis.…”
Section: Rationale For Researchmentioning
confidence: 95%
See 1 more Smart Citation
“…Neither ciclosporin nor mycophenolate mofetil is very effective in controlling joint manifestations of JIA in children. 19 More recently, animal models and corroborative human evidence 23 support the role of tumour necrosis factor alpha (TNF-α) in the aetiopathogenesis of uveitis and, moreover, the potential value of its inhibition as a therapeutic intervention. 24 Studies on experimental models of autoimmune uveitis have demonstrated that TNF-α plays a pivotal role in pathogenesis of intraocular inflammation, 23 which has been borne out in treatment of adult uveitis.…”
Section: Rationale For Researchmentioning
confidence: 95%
“…Despite the scarce evidence, MTX has become the mainstay of treatment for JIA-uveitis. 19 However, up to 15-50% of children will have refractory uveitis in spite of optimal therapy with MTX. [16][17][18] In a small study, 20 some 30% of patients started on MTX for JIA-associated uveitis did not achieve disease control during the first year of therapy and, even when remission was achieved with MTX, nearly 70% of patients will later relapse, suggesting that only 4 out of 22 (18%) patients achieved total remission.…”
Section: Rationale For Researchmentioning
confidence: 99%
“…Systematic review of the evidence for the effectiveness of MTX in JIA patients is restricted to joint involvement [14], but not in paediatric uveitis. Despite the scarce evidence, MTX has become the mainstay of treatment for JIA-associated uveitis [19]. However, about 15% to 50% of affected children will have refractory uveitis in spite of optimal therapy with MTX [16-18].…”
Section: Introductionmentioning
confidence: 99%
“…However, their use remains restricted because of intolerability due to adverse reactions and little evidence that they rescue MTX-refractory patients. In addition, neither ciclosporin nor MMF is very effective in controlling joint manifestations in children [19]. More recently, animal models and corroborative human evidence [23] support the role of tumour necrosis factor α (TNF-α) in the aetiopathogenesis of uveitis and, moreover, the potential value of inhibiting TNF-α as a therapeutic intervention [24].…”
Section: Introductionmentioning
confidence: 99%
“…If corticosteroids revamped the treatment of intraocular inflammation in the early 1950s, immunosuppression has ushered in a new era of therapy for patients with severe intraocular inflammation and now with targeted therapy using biologics in specific uveitic entities we are probably embarking on much specialised stratified care. [45121819202122]…”
Section: Current and Potential ‘Tailored’ Treatment Of Non-infectiousmentioning
confidence: 99%